An Extended Approach for the Development of Fluorogenic trans‐Cyclooctene–Tetrazine Cycloadditions. (7th March 2019) - Siegl, Sebastian J.; Galeta, Juraj; Dzijak, Rastislav; Vázquez, Arcadio; Del Río‐Villanueva, Miguel; Dračínský, Martin; Vrabel, Milan
Abstract: Inverse‐electron‐demand Diels–Alder (iEDDA) cycloaddition between 1, 2, 4, 5‐tetrazines and strained dienophiles belongs among the most popular bioconjugation reactions. In addition to its fast kinetics, this cycloaddition can be tailored to produce fluorescent products from non‐fluorescent starting materials. Here we show that even the reaction intermediates formed in iEDDA cycloaddition can lead to the formation of new types of fluorophores. The influence of various substituents on their photophysical properties and the generality of the approach with use of various trans ‐cyclooctene derivatives were studied. Model bioimaging experiments demonstrate the application potential of fluorogenic iEDDA cycloaddition. Abstract : Lighting up : 1, 2, 4, 5‐Tetrazines bearing electron‐donating substituents react with various trans ‐cyclooctenes (TCOs) to form fluorescent products without the need for attachment of an extra fluorophore moiety. The photophysical properties of the products depend on the tetrazine and the TCO structure. The developed chemistry was successfully applied to bioimaging.